Peran Kewirausahaan dalam Pertumbuhan Ekonomi Islam di Indonesia - Zakiyah Darojah; M. Didanul Quro’i; Dita Kartika Dewi (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2018)
In economic activities, Islam encourages its people to be entrepreneurial, as taught in the Qur'an and hadith. In entrepreneurship, a person must have noble qualities, and it is forbidden to do entrepreneurship in a dishonest and unkind way. To become a successful entrepreneur, one should have a proactive, productive, empowering, hands-on (like to give) nature, humble, creative, and innovative. Entrepreneurship has become a concern of the government, especially Small and Medium Enterprises (SMEs), reducing the number of unemployment and poverty in Indonesia. Entrepreneurship has its role in Indonesia's economic growth, namely increasing productivity. Entrepreneurship also affects the development of the Islamic economy in Indonesia. That can develop sharia financial services, which include sharia banking, sharia cooperatives, sharia insurance, sharia mutual funds, etc., proves that entrepreneurship has a positive role in the growth of the Islamic economy in Indonesia.